Geodetic Evidence That Mercury Has A Solid Inner Core. Issue 7 (10th April 2019) - Genova, Antonio; Goossens, Sander; Mazarico, Erwan; Lemoine, Frank G.; Neumann, Gregory A.; Kuang, Weijia; Sabaka, Terence J.; Hauck, Steven A.; Smith, David E.; Solomon, Sean C.; Zuber, Maria T.
Abstract: Geodetic analysis of radio tracking measurements of the MErcury Surface, Space ENvironment, GEochemistry, and Ranging spacecraft while in orbit about Mercury has yielded new estimates for the planet's gravity field, tidal Love number, and pole coordinates. The derived right ascension ( α  = 281.0082° ± 0.0009°; all uncertainties are 3 standard deviations) and declination ( δ  = 61.4164° ± 0.0003°) of the spin pole place Mercury in the Cassini state. Confirmation of the equilibrium state with an estimated mean (whole planet) obliquity ϵ of 1.968 ± 0.027 arcmin enables the confident determination of the planet's normalized polar moment of inertia (0.333 ± 0.005), which indicates a high degree of internal differentiation. Internal structure models generated by a Markov Chain Monte Carlo process and consistent with the geodetic constraints possess a solid inner core with a radius ( r i c ) between 0.3 and 0.7 that of the outer core ( r oc ). Key Points: New solution for Mercury's gravity field provides crucial information on the planet's tidal response and orientation New determination of Mercury's pole position fully satisfies the equilibrium Cassini state New estimate of Mercury's polar moment of inertia supports the presence of a large solid inner core